Role of nasal high-frequency oscillatory ventilation in a premature infant with severe bronchopulmonary dysplasia - Akiho Ueda-Kuramochi; Kazumi Morisawa; Takeshi Arimitsu; Kazuma Shimura; Kaori Hara-Isono; Takane Kin; Mariko Hida (Respiratory Medicine Case Reports)
To prevent the worsening of bronchopulmonary disease (BPD), early extubation is desirable. However, in extremely preterm infants, BPD tends to become severe, making early extubation difficult and leading to prolonged intubation. Even if the intubation period is prolonged, feasible respiratory strategies for extubation in extremely preterm infants during the chronic phase of severe BPD are necessary. In preterm infants, nasal high-frequency oscillatory ventilation (NHFOV) can support breathing after extubation immediately after birth, but whether NHFOV is effective as respiratory support after extubation in the chronic phase of severe BPD in extremely preterm infants is unclear. Especially for extremely preterm births or infants with extremely low birth weights, early extubation is difficult. Although such infants' postmenstrual age and weight increase during long-term ventilator support, their respiratory function is very poor compared with that of preterm infants born at a gestational age equivalent to such infants' postmenstrual age owing to substantial lung damage caused by the ventilator. For this reason, extubation in the chronic phase of BPD may also be challenging. In this report, we describe a case of a marginally viable infant who was born at 23 weeks’ gestation weighing 374 g, required 2 months of intubation after birth owing to severe BPD, and was successfully extubated using NHFOV. This case report suggests that NHFOV may be an effective respiratory strategy for very low birth weight infants with severe BPD.